Postliberalization Indian novels in English politics of global reception and awards - Viswamohan, Aysha Iqbal (Anthem Press, 2013)
'Postliberalization Indian Novels in English: Politics of Global Reception and Awards' is a critical handbook that focuses on trends in contemporary Indian novels and discusses the global reception of these works. The volume provides a systematic approach to the study of Indian novelists that have not been (with certain exceptions) extensively examined